Ferry scheduling model using linear programming technique - Wan Mohd Khairy Adly, Wan Zaimi; Mohd Syafarudy, Abu; Ahmad Kadri, Junoh; Wan Nor Munirah, Ariffin (Institute of Electrical and Electronics Engineers (IEEE), 2011)
Link to publisher's homepage at http://ieeexplore.ieee.org/